Quality Improvement of Catfish Floss (Clarias gariepinus) Through Oil Reduction Technology with Spinner and Press Tools - Romadhon Romadhon; Ulfah Amalia; Apri Dwi Anggo (Journal Omni-Akuatika, 2019)
The nutritional content of catfish allows this freshwater fish to be processed into a variety of products, one of which is fish floss. Fish floss is a product that is popular among the people so that many use it for sale and increase income. However, unfortunately many fish floss products that are of poor quality, for example, oil appeared in the packaging which consequently makes the fish floss products quickly rancid. The purpose of this study was to determine the optimal shelf life of floss catfish with the best quality. The experimental laboratories of this study was divided into three treatments: spinnered, pressed and combination of spinnered and pressed. The quality of fish floss were observed every 12 days for 48 days.The results showed that there were significantly effect of floss catfish with different treatments of oil reduction. The best quality of floss catfish was achieved at 36 days storaging, with an average value of water content 4.99%, 28.39% of protein content, 9.15% of fat content, 4.99 meq kg-1 of peroxide value and total plate count 6.9 x 10-3 cfu g-1.